2015
DOI: 10.1038/srep12258
|View full text |Cite
|
Sign up to set email alerts
|

Association of astrocytes with neurons and astrocytes derived from distinct progenitor domains in the subpallium

Abstract: Astrocytes play pivotal roles in metabolism and homeostasis as well as in neural development and function in a manner thought to depend on their region-specific diversity. In the mouse spinal cord, astrocytes and neurons, which are derived from a common progenitor domain (PD) and controlled by common PD-specific transcription factors, migrate radially and share their final positions. However, whether astrocytes can only interact with neurons from common PDs in the brain remains unknown. Here, we focused on sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…This morphological classification corresponds to regional heterogeneity, because fibrous and protoplasmic astrocytes generally segregate in white matter and gray matter, respectively. Recent studies demonstrated that astrocytes are allocated to spatially distinct domains in the developing brain (Tsai et al, 2012 ; Molofsky et al, 2014 ; Bayraktar et al, 2015 ) and can only interact with neurons derived from the same domain (Torigoe et al, 2015 ). Given that astrocytic regional domains coordinate post-natal neural circuit formation and regulate eventual neuronal activity, astrocytic regional heterogeneity can also be regarded as functional heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…This morphological classification corresponds to regional heterogeneity, because fibrous and protoplasmic astrocytes generally segregate in white matter and gray matter, respectively. Recent studies demonstrated that astrocytes are allocated to spatially distinct domains in the developing brain (Tsai et al, 2012 ; Molofsky et al, 2014 ; Bayraktar et al, 2015 ) and can only interact with neurons derived from the same domain (Torigoe et al, 2015 ). Given that astrocytic regional domains coordinate post-natal neural circuit formation and regulate eventual neuronal activity, astrocytic regional heterogeneity can also be regarded as functional heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, astrocytes from gray and white matter react differently to SWI (Mattugini et al, ). This could be due to preexisting differences between astrocytes from distinct brain regions (Boisvert, Erikson, Shokhirev, & Allen, ; Chai et al, ; Itoh et al, ; John Lin et al, ; Lanjakornsiripan et al, ; Morel et al, ; Torigoe, Yamauchi, Zhu, Kobayashi, & Murakami, ). Another demonstration of different molecular classes of reactive astrocytes came from the Barres laboratory.…”
Section: Do All Astrocytes React the Same Way?mentioning
confidence: 99%
“…Boisvert, Erikson, Shokhirev, & Allen, 2018;Chai et al, 2017;Itoh et al, 2018;John Lin et al, 2017;Lanjakornsiripan et al, 2018;Morel et al, 2017;Torigoe, Yamauchi, Zhu, Kobayashi, & Murakami, 2015). Another demonstration of different molecular classes of reactive astrocytes came from the Barres laboratory.…”
mentioning
confidence: 99%
“…In other brain regions, astrocyte heterogeneity appears to be more complex. In the striatum, intermixed astrocytes and neurons from multiple progenitor pools interact indiscriminately yet astrocytes show selective interactions with specific circuits (Martín et al, 2015 ; Torigoe et al, 2015 ). Single-cell RNAseq of the striatum indicates that unlike other cells of the striatum, astrocytes do not segregate into discrete populations and therefore do not appear to form well-defined subtypes (Gokce et al, 2016 ).…”
Section: Environmental Cues and Intraregional Heterogeneity Of Astrocmentioning
confidence: 99%